2009
DOI: 10.1021/jp9041167
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of CdSe Nanoparticles Adsorbed on Au Electrodes by an Organic Linker: Fermi Level Pinning of the HOMO

Abstract: Assemblies of CdSe nanoparticles (NPs) on a dithiol-coated Au electrode were created, and their electronic energetics were quantified. This report describes the energy level alignment of the filled and unfilled electronic states of CdSe nanoparticles with respect to the Au Fermi level. Using cyclic voltammetry, it was possible to measure the energy of the filled states of the CdSe NPs with respect to the Au substrate relative to a Ag/AgNO 3 electrode, and by using photoemission spectroscopy, it was possible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
59
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 38 publications
13
59
0
Order By: Relevance
“…Such discrepancy could be explained by (i) impact of recombination [24], (ii) influence of specific adsorption of ions and dipoles of solvent [31], and (iii) non-negligible difference between E c and E Fn for CdSe QDs. Nevertheless, the obtained constancy in E v position regardless of the CdSe QD size is in a good agreement with the above-cited works [30][31][32][33][34][35][36].…”
Section: Photoelectrochemical Properties Of Cdse Films In Na 2 So 3 Solutionsupporting
confidence: 92%
See 1 more Smart Citation
“…Such discrepancy could be explained by (i) impact of recombination [24], (ii) influence of specific adsorption of ions and dipoles of solvent [31], and (iii) non-negligible difference between E c and E Fn for CdSe QDs. Nevertheless, the obtained constancy in E v position regardless of the CdSe QD size is in a good agreement with the above-cited works [30][31][32][33][34][35][36].…”
Section: Photoelectrochemical Properties Of Cdse Films In Na 2 So 3 Solutionsupporting
confidence: 92%
“…Note that the obtained E c and E v values are anodically shifted by appr. 0.5 V in comparison with the values provided by theoretical calculations [30] and experimental findings (ultraviolet photoelectron emission spectroscopy [31][32][33], cyclic voltammetry in non-aqueous solutions [34][35][36]). Such discrepancy could be explained by (i) impact of recombination [24], (ii) influence of specific adsorption of ions and dipoles of solvent [31], and (iii) non-negligible difference between E c and E Fn for CdSe QDs.…”
Section: Photoelectrochemical Properties Of Cdse Films In Na 2 So 3 Solutionmentioning
confidence: 55%
“…103 Recently, Markus et al compared energy level positions for CdSe nanocrystals as measured by CV and by photoemission spectroscopy as a more sophisticated method. 109 Reasonable agreement was found, but as an interesting result the authors observed that the valence band became independent of the particle size due to a pinning effect when the nanoparticles were measured on an Au substrate. 109 This points out that interactions with a substrate may also influence the electrochemical measurements when studying thin films.…”
Section: Charge Separation In Polymer/nanoparticle Donor/acceptor Blendsmentioning
confidence: 96%
“…Here, the HOMO energy is defined by the cutoff in the LEPET spectra, while the LUMO is defined by the peak in the TPPE spectra. 18 The HOMO-LUMO energy gaps obtained (6 nm). The difference LEPET spectra (below the Fermi level) that are obtained by subtracting the spectrum of the DT/Au, and TPPE spectra (above the Fermi level) of (c) CdSe (6 nm) and (d) CdSe (3.7 nm).…”
mentioning
confidence: 99%
“…It is expected that the size of the core will affect the properties of its wave function in a c/s NP. [18][19][20][21] To investigate the size effect we used small CdSe/ ZnS c/s NPs with an average diameter of 3.8 nm. Figure 5d shows the PL of these NPs on DT/Au and when DT molecules are adsorbed on the particles.…”
mentioning
confidence: 99%